2021
DOI: 10.1051/kmae/2021012
|View full text |Cite
|
Sign up to set email alerts
|

Plant morphological traits and competition index comparisons of three invasive and native submerged plants

Abstract: The submerged species Carolina fanwort (Cabomba caroliniana) has attracted considerable attention in Lake Taihu Basin (LTB), China. This species was widely used as a garden plant until 2016, when it was identified as invasive. In this study, we conducted a mesocosm experiment to compare the morphological traits, includingtotal dry mass, shoot/root (S/R) ratio, relative growth rate (RGR) and competition index log response ratio (ln RR), of C. caroliniana and two frequently co-occurring native submerged plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, the performance of C. caroliniana was better and more stable than those of M. spicatum or H. verticillata in response to the low underwater PAR (for instance, 50%, 25% and 5% underwater PAR) treatments. According to a previous study, C. caroliniana does not have a better competitive ability than native co‐occurring submerged plants (Huang et al, 2021), but it is relatively resistant to herbivory by grass‐feeding snails (Huang et al, 2022). In this study, we provide new insights into the possible invasion mechanism of C. caroliniana under low underwater PAR levels, which may improve the ability to predict its invasion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the performance of C. caroliniana was better and more stable than those of M. spicatum or H. verticillata in response to the low underwater PAR (for instance, 50%, 25% and 5% underwater PAR) treatments. According to a previous study, C. caroliniana does not have a better competitive ability than native co‐occurring submerged plants (Huang et al, 2021), but it is relatively resistant to herbivory by grass‐feeding snails (Huang et al, 2022). In this study, we provide new insights into the possible invasion mechanism of C. caroliniana under low underwater PAR levels, which may improve the ability to predict its invasion.…”
Section: Discussionmentioning
confidence: 98%
“…Five extra buckets with one of the three plants were also set up at the same time to measure the initial dry mass when the experiment started after 1 week of cultivation. Although culturing the three species independently is the ideal approach, the results of a previous study (Huang et al, 2021) performed in 2018 showed that competition among the three species under these conditions is relatively low, rendering coculturing acceptable.…”
Section: Methodsmentioning
confidence: 99%